Using scenario-based assessments to examine the feasibility of integrating preventive nutrition services through the primary health care system in Bangladesh - Nguyen, Phuong Hong; Pramanik, Priyanjana; Billah, Sk Masum; Avula, Rasmi; Ferdous, Tarana E.; Sarker, Bidhan K.; Rahman, Musfikur; Ireen, Santhia; Mahmud, Zeba; Menon, Purnima; Ash, Deborah (Wiley, 2022)
The National Nutrition Services of Bangladesh aims to deliver nutrition services through the primary health care system. Little is known about the feasibility of reshaping service delivery to close gaps in nutrition intervention coverage and utilization. We used a scenario-based feasibility testing approach to assess potential implementation improvements to strengthen service delivery. We conducted in-depth interviews with 31 service providers and 12 policymakers, and 5 focus group discussions with potential beneficiaries. We asked about the feasibility of four hypothetical scenarios for preventive and promotive nutrition service delivery: community-based events (CBE) for pregnant women, well-child services integrated into immunization contacts; CBE for well-children, and well-child visits at facilities. Opinions on service delivery platforms were mixed; some recommended new platforms, but others suggested strengthening existing delivery points. CBE for pregnant women was perceived as feasible, but workforce shortages emerged as a key barrier. Challenges such as equipment portability, upset children and a fast-moving service environment suggested low feasibility of integrating nutrition into outreach immunization contacts. In contrast, CBE and facility-based well-child visits emerged as feasible options, conditional on having the necessary workforce, structural readiness and budget support. On the demand side, enabling factors include using interpersonal communication and involving community leaders to increase awareness, organizing events at a convenient time and place for both providers and beneficiaries, and incentives for beneficiaries to encourage participation. In conclusion, integrating preventive and promotive nutrition services require addressing current challenges in the health system, including human resource and logistic gaps, and investing in creating demand for preventive services.